Solid Fuel Char Production via Pyrolysis Process of Oily Sludge Produced as a Resulted in Storage Tanks at North Refineries Company Baiji - Abdulqader, Mahmod A.; Habeeb, Omar Abed; Dheab, Mohammed Sarhan; Saber, Shihab Ezzuldin M.; Rabet, Asaad Owayez; Mohammed, Gazwan J.; Saleh, A. H. (Journal of Petroleum Research and Studies, 2022)
The oily sludge contains a toxics material. It has an impact effect to the environment and worker’s health. Therefore, treatment the residue oily sludge in the refineries storage tanks and convert it to useful product, is an important task. Oily sludge (OS) sample was obtained from North Refineries Company (NRC) Baiji which produced about 3000-3500 m3/ year. In this study, different range of pyrolysis temperatures have been applied (300, 500, 700, and 900 °C). The parameters have been investigated the efficiency of char produced from OS. The operation conditions of (20 g, 700 °C, and 1.5 h, under N2 pressure) are investigated. The calorific value was enhanced from 9.125 to 17.247 MJ.kg-1 with an increased rate 89.0 %. The fuel ratio was increased from 0.78 of OS to 0.97 around 24.35 % increased percentage of char at 700 °C. Finally, the energy recovery was enhanced at maximum value 1.909 % of char at 700 °C. The results show the fuel properties were upgraded to burn with a small amount of CO2.